2016
DOI: 10.1186/s41235-016-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning to interpret topographic maps: Understanding layered spatial information

Abstract: Novices struggle to interpret maps that show information about continuous dimensions (typically latitude and longitude) layered with information that is inherently continuous but segmented categorically. An example is a topographic map, used in earth science disciplines as well as by hikers, emergency rescue operations, and other endeavors requiring knowledge of terrain. Successful comprehension requires understanding that continuous elevation information is categorically encoded using contour lines, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…When interpreting a geologic map, the expert's domain knowledge interacts with his or her spatial skills to result in an advanced level of perceptual processing (see Goldstone &Barsalou, 1998 andBarrett, Lindquist, &Gendron, 2007 for further examples on the interaction of perceptual and conceptual processing). For instance, interpreting topographical information on the map involves skill in understanding how elevation information is denoted using contour lines, and also skill in visualizing the represented topography in 3D (Atit, Weisberg, Newcombe, & Shipley, 2016;Liben & Titus, 2012). The expert's approach to interpreting topographical information involves identifying meaningful patterns in the contour lines that represent topographical structures (e.g., contour lines in concentric circles represent a hill) (Chang, Antes, & Lenzen, 1985), and then visualizing those structures in 3D (Eley, 1981(Eley, , 1983.…”
Section: The Influence Of Domain Knowledge and Context On Spatial Thimentioning
confidence: 99%
See 1 more Smart Citation
“…When interpreting a geologic map, the expert's domain knowledge interacts with his or her spatial skills to result in an advanced level of perceptual processing (see Goldstone &Barsalou, 1998 andBarrett, Lindquist, &Gendron, 2007 for further examples on the interaction of perceptual and conceptual processing). For instance, interpreting topographical information on the map involves skill in understanding how elevation information is denoted using contour lines, and also skill in visualizing the represented topography in 3D (Atit, Weisberg, Newcombe, & Shipley, 2016;Liben & Titus, 2012). The expert's approach to interpreting topographical information involves identifying meaningful patterns in the contour lines that represent topographical structures (e.g., contour lines in concentric circles represent a hill) (Chang, Antes, & Lenzen, 1985), and then visualizing those structures in 3D (Eley, 1981(Eley, , 1983.…”
Section: The Influence Of Domain Knowledge and Context On Spatial Thimentioning
confidence: 99%
“…For instance, mental rotation is critical to problem-solving in chemistry (e.g., Harle & Towns, 2011;Stieff, 2007) and surgery (Hegarty et al, 2007), as well as mathematics (e.g., Gilligan, Hodgkiss, Thomas, & Farran, 2017;Lombardi, Casey, Pezaris, Shadmehr, & Jong, 2019;Lowrie & Logan, 2018). On the other hand, field-relevant spatial skills that involve specific tools of representation reflect disciplinary core ideas that are important for and specific to reasoning and understanding within the STEM discipline of interest, such as skills for interpreting 2D diagrams in chemistry (e.g., Padalkar & Hegarty, 2015;Stieff, 2011;Stull & Hegarty, 2016) and skills for interpreting topographic maps in geology (e.g., Atit et al, 2016;Chang et al, 1985;Eley, 1983). As outlined by the National Research Council (2012a) framework, both crosscutting concepts (e.g., fundamental spatial skills) and core disciplinary ideas (e.g., field-relevant spatial skills) are needed for meaningful learning within the STEM disciplines.…”
Section: Implications For Stem Educationmentioning
confidence: 99%
“…While topographic maps have been and continue to be used for teaching cartography, researchers such as Griffin and Lock [5] found that there are inherent perceptual problems in contour line interpretation. These difficulties have generated problems of frustration/motivation among students [6][7][8][9]. Further, issues such as landform representation, spatial skills acquisition, or processes of spatial knowledge construction with different forms of relief representation continue to be active fields of research including recent works by Carbonell [10,11], Collins [12], Tillman, Albrecht and Wunderlich [13], Eynard and Bernhard [14], and Brooke and Bernhard [3].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mental rotation is critical to problem solving in chemistry (e.g., Harle & Towns, 2011;Stieff, 2007) and surgery (Hegarty et al, 2007), as well as mathematics (e.g., Gilligan, Hodgkiss, Thomas, & Farran, 2019;Lombardi et al, 2019;Lowrie & Logan, 2018). On the other hand, field-relevant spatial skills that involve specific tools of representation reflect disciplinary core ideas that are important for and specific to reasoning and understanding within the STEM discipline of interest, such as skills for interpreting 2D diagrams in chemistry (e.g., Padalkar & Hegarty, 2015;Stieff, 2011;Stull & Hegarty, 2016) and skills for interpreting topographic maps in geology (e.g., Atit et al, 2016;Chang, Antes, & Lenzen, 1985;Eley, 1983). As outlined by the NRC (2012) framework, both crosscutting concepts (e.g., fundamental spatial skills) and core disciplinary ideas (e.g., fieldrelevant spatial skills), are needed for meaningful learning within the STEM disciplines.…”
Section: Implications For Stem Educationmentioning
confidence: 99%